Manchester Museum hands back 174 objects to Indigenous Australian islanders - Brown, Mark; correspondent, Mark Brown North of England (The Guardian, 2023)
Return of items to Anindilyakwa community hailed as landmark example of cultural repatriation
Keywords: 2023-09 September; Australia news; Culture; England; Indigenous Australians; Indigenous peoples; Manchester; Museums; UK news